High directional optical transmitter with phased array of nanoptical emitters and efficient error correction for long distance space communications - Elisa Bazzani; Anna Valeria Guglielmi; Roberto Corvaja; Nicola Laurenti; Filippo Romanato; Gianluca Ruffato; Andrea Vogliardi; Giuseppe Vallone; Lorenzo Vangelista; Paolo Villoresi (Physical Review Research)
Communications in space are rapidly increasing in both capacity and extension. A satellite network in space calls for efficient and lightweight optical transmitters, suitable to communicate over distances going from the low-Earth-orbit to interplanetary links and beyond. To this aims, here we study the use of novel resources as an array of nanoptical coupler from guided sources and modulators to free space modes, that is phased with a suitable correction systems as well as efficient coding with error corrections capable of bearing large values of losses. We develop a method for designing such an array, which achieve a main lobe divergence of 1 µrad. We also discuss the lower and upper limits of the beam steering technique as a function of the array and emitter size, respectively. The optimization of grating couples (GCs) resulted an apodized structure with approximately 0.7 coupling efficiency and 70-µm beam waist. We also demonstrate the feasibility of phase correction and polarization modulation of the output mode by means of metalenses. The resulting link budget in terms of received photons on the Earth sets exceptional conditions for the digital optical communication system, for which a power efficient modulation scheme such as pulse position modulation (PPM) is considered. Here, we assess the PPM performance and we propose suitable channel coding schemes, essential to reduce the high bit error rate obtained in few-photon regime at the receiver.